Pengembangan Komik Digital berbasis Canva untuk Meningkatkan Kemampuan Penalaran Proporsional Peserta Didik SMP - Latifah, Anisa Tri; H. Supratman; Diar Veni Rahayu (LPPM Universitas Advent Indonesia, 2024)
Digital comics are a medium presented in the form of illustrated stories with certain characters which can be used to convey information or messages via electronic media. The aim of this research is to improve the proportional reasoning abilities of junior high school students through learning using Canva-based digital comic media. This type of research is R & D (Research & Develop) with the ADDIE model (analysis, design, develop, implementation, evaluation). The instruments used are test and non-test instruments. The subjects in this research were class VII students at one of the Tasikmalaya Regency Middle Schools. The results of this Research and Development were then analyzed for the effectiveness of the learning media, resulting in a